2018
DOI: 10.1159/000488832
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Attenuates Myocardial Hypertrophy in Spontaneously Hypertensive Rats via the C/EBPβ/PGC-1α/UCP3 Pathway

Abstract: Background/Aims: Many clinical and experimental studies have shown that treatment with statins could prevent myocardial hypertrophy and remodeling induced by hypertension and myocardial infarction. But the molecular mechanism was not clear. We aimed to investigate the beneficial effects of atorvastatin on hypertension-induced myocardial hypertrophy and remodeling in spontaneously hypertensive rats (SHR) with the hope of revealing other potential mechanisms or target pathways to interpret the pleiotropic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…These results were supported by previous reports that PGC-1α activation alleviated cardiac fibrosis and remodeling. 32 , 33 , 34 We also demonstrated that Rb-1 mediated miR-199a-3p in promoting cardiomyocyte hypertrophy with an increase of nuclear translocation of transcription factor E2F2 in NMVCs. Adult mammalian cardiomyocytes may reenter the cell cycle and cause cardiac hypertrophy, 35 , 36 and activation of the Rb/E2f signal was reported to participate in cell-cycle progression of cardiomyocytes 37 , 38 and cardiomyocyte hypertrophy.…”
Section: Discussionsupporting
confidence: 52%
“…These results were supported by previous reports that PGC-1α activation alleviated cardiac fibrosis and remodeling. 32 , 33 , 34 We also demonstrated that Rb-1 mediated miR-199a-3p in promoting cardiomyocyte hypertrophy with an increase of nuclear translocation of transcription factor E2F2 in NMVCs. Adult mammalian cardiomyocytes may reenter the cell cycle and cause cardiac hypertrophy, 35 , 36 and activation of the Rb/E2f signal was reported to participate in cell-cycle progression of cardiomyocytes 37 , 38 and cardiomyocyte hypertrophy.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, ventricular remodeling is a risk factor of various severe arrhythmias, as well as sudden mortality (24). Owing to improved compliance, AM + AT have been used for treating hypertension and hyperlipidemia, and can protect vascular smooth muscle and myocardium from remodeling (25,26). Caduet is a single pill containing AM and AT, which blocks Ca 2+ transmembrane influx, inhibits β-Hydroxy β-methylglutaryl-coenzyme A reductase, decreases vascular resistance and reverses ventricular remodeling (27).…”
Section: Discussionmentioning
confidence: 99%
“…Since PGC-1α was also upregulated by THC, the interactions between PGC-1α and UPR mt were further investigated. PGC-1α mediates the anticardiac hypertrophic role of several medicines [37,38]. It also exerts a cardioprotective role in ischemia and reperfusion-induced and exhaustive exerciseinduced heart injury due to its antioxidant activity [39,40].…”
mentioning
confidence: 99%